OPTIMALISASI EKONOMI PEMILIHAN POLA TANAM UNGGULAN DI KABUPATEN JEMBER - Muhammad Firdaus (RELASI : JURNAL EKONOMI, 2013)
This study aims to determine the type of commodity and  planting patterns that can provide the maximum benefit to the farmers. Determination ofcommodities using the Location Quotient while typing planting patterns using linear programming and sensitivity analysis . The results showed that the planting patterns: paddy-horticulture-horticulture conducted in District of Ajung, Jombang, Kencong, Ledokombo, Panti, Patrang, Rambipuji, Semboro, Sumberbaru, and Tempurejo; paddy-horticulture-“palawija” planting pattern conducted in the district of Mayang, Mumbulsari, and Silo; paddy-tobacco na oogst-horticulture planting pattern conducted in District of Ambulu, Balung, Jenggawah, Kaliwates,Puger, Sumbersari, Tanggul, Umbulsari, and Wuluhan; paddy-tobacco na oogst-“palawija” done in District Jelbuk; paddy-tobacco kasturi-horticulture conducted in District of Arjasa, Bangsalsari, Kalisat, Pakusari, Sukorambi, and Sukowono;paddy-tobacco kasturi-“palawija” done in District of Sumberjambe, and planting pattern: paddy-“palawija”-“palawija” should be done in the District of Gumukmas.